Safe delivery kits and newborn infection in rural Ethiopian communities - Won Ju Hwang; Tae Hwa Lee (Frontiers in Public Health, 2024)
ObjectivesOur goal in this study to investigate the impacts of using safe delivery kits, along with education on their appropriate use, has on preventing newborn and maternal infection.DesignA cross-sectional study.SettingParticipants, and Interventions: we conducted the study on 23 sites across a rural district in Oromia Region, Ethiopia. Safe delivery kits were distributed by health extension workers. Participants comprised 534 mothers between the ages of 17 and 45 years, who were given a safe delivery kit at 7 months’ pregnancy for use during their subsequent delivery. Data collection was performed by the trained interviewers in rural Ethiopian communities.ResultsMultiple logistic regression analyses showed an independent association between using the cord tie provided in the kits and decreased newborn infection. Specifically, newborns whose mothers used the cord tie were 30 times less likely to develop cord infection than those not using the cord tie in the kits. Further, mothers who received education regarding safe delivery kit use had lower rates of puerperal infection.ConclusionSingle-use delivery kits, when combined with education regarding the appropriate means of using the kit, can decrease the likelihood of maternal infection.Implications for nursingNurses and health extension workers in low and middle-income countries should educate mothers on safe delivery kits by providing information regarding their usefulness and the importance of correct and consistent use. Implications for Health Policy: our findings emphasize the need for further interventions in vulnerable countries designed to increase the rate of hygienic birthing practices for deliveries outside health-care facilities.